The federal budget - Hiber, Amanda (Opposing viewpoints series, 2010)
This volume explores the topics relating to the federal budget of the United States by presenting varied expert opinions that examine many of the different aspects that comprise these issues. The viewpoints are selected from a wide range of highly respected and often hard-to-find sources and publications. Allows the reader to attain the higher-level critical thinking and reading skills that are essential in a culture of diverse and contradictory opinions